MANAJEMEN PERKANDANGAN SAPI PERAH DI UNIT PELAKSANA TEKNIS DINAS BALAI PENGEMBANGAN BIBIT PAKAN TERNAK DAN DIAGNOSTIK KEHEWANAN (UPTD BPBPTDK) DINAS PERTANIAN YOGYAKARTA - , WIRDATUL JANNAH, drh. Untoro, M. S ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The aim of this study is to know cage management in UPTD BPBPTDK of agricultural department of Yogyakarta. Consist of cage construction, sanitation, untility and equipment, waste and health of milch cow. This study is based on measurement and direct observation in the livestock. The method os is study is direct observational past data review and interview with the responsible person of the livestock. The data taken is about cage disease and all of supporting data. The data taken between January 2010 until april 2013. There were 16 lactating milch cow,16 heifer cow and 11 calfs. From the data we can conclude that the cage management in the livestock is good enough but still has weaknesses that need to be fixed.